The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2136/sssaj2011.0407
|View full text |Cite
|
Sign up to set email alerts
|

“The Changing Model of Soil” Revisited

Abstract: In 1961, the late Marlin G. Cline wrote a remarkable essay entitled, “The Changing Model of Soil” for the 25th Anniversary Issue of the Soil Science Society of America Proceedings. Cline was most impressed with how geomorphology was enriching pedology, and with the increasingly sophisticated views of soil time and of the processes of soil formation. We revisit Cline's general objectives by re‐evaluating the changing model of soil from the perspective of the early 21st century, and by taking stock of the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 97 publications
4
93
0
Order By: Relevance
“…fluxdata.org/partner-networks/long-term-soil-experiments/, last access: 2 August 2018), there are many hundreds of long-term agricultural research sites worldwide that are monitoring the sustainability of agricultural production over decadal timescales (Richter and Yaalon, 2012). These experiments study effects of tillage practices, rotations, and long-term amendments of fertilizers and organic materials such as manures and sludges on soils, microbial communities, biochemical and physical fluxes (such as those affecting soil water and heat regimes), and crop productivity.…”
Section: Origins Of Environmental Research Networkmentioning
confidence: 99%
“…fluxdata.org/partner-networks/long-term-soil-experiments/, last access: 2 August 2018), there are many hundreds of long-term agricultural research sites worldwide that are monitoring the sustainability of agricultural production over decadal timescales (Richter and Yaalon, 2012). These experiments study effects of tillage practices, rotations, and long-term amendments of fertilizers and organic materials such as manures and sludges on soils, microbial communities, biochemical and physical fluxes (such as those affecting soil water and heat regimes), and crop productivity.…”
Section: Origins Of Environmental Research Networkmentioning
confidence: 99%
“…Nave et al [9] reported a mixed response to harvest in deeper soil (20-100 cm depth), ranging from a slight average decrease (−5%) in studies that reported C pools to a large average increase (+20%) in studies that reported only C concentration. Several recent reviews have highlighted the need for greater sampling of deep soil [26][27][28], especially as the shifting paradigm of SOM research has come to reject the assumption that deep soil C cannot not change on timescales relevant to anthropogenic C emissions [29][30][31]. Resolving the response of deep soil horizons to harvesting is important because these horizons occupy a much greater volume than surface O and A horizons.…”
Section: Introductionmentioning
confidence: 99%
“…Brum et al (2013) found that an anthrome category (village) was a better predictor of the distribution of threatened amphibians than climate. The anthromes framework has also been suggested as a resource for conserving tropical forest biodiversity (Gardner et al, 2009), guiding management of sustainable agricultural systems (Richter & Yaalon, 2012) and identifying the relationships between multiple ecosystem services across heterogeneous land uses (Bennett et al, 2009).…”
Section: Proposalmentioning
confidence: 99%